2022
DOI: 10.1002/1873-3468.14444
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cells for studying mitochondrial diseases in the heart

Abstract: Mitochondrial dysfunction is known to contribute to a range of diseases, and primary mitochondrial defects strongly impact high‐energy organs such as the heart. Platforms for high‐throughput and human‐relevant assessment of mitochondrial diseases are currently lacking, hindering the development of targeted therapies. In the past decade, human‐induced pluripotent stem cells (iPSCs) have become a promising technology for drug discovery in basic and clinical research. In particular, human iPSC‐derived cardiomyocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…In the last decade, with the booming number of congenital and acquired metabolic disorders identified [71], the need to develop in vitro disease models via patient-derived hiPSCs to study pathogenic mechanisms and screen drugs preclinically is widely increasing. In the field of nucleotide sugar biosynthesis defects, to date only few hiPSC-based studies have been reported, specifically targeting phosphomannomutase 2 (PMM2) deficiency and UDP-glucose pyrophosphorylase (UGP2) deficiency [72][73][74], while they are more extensively used to model other inborn errors of metabolism, such as Pompe disease or mitochondrial disorders [75][76][77][78][79][80][81][82]. Nonetheless, despite the rapidly increasing interest in hiPSCs and hiPSC-derived models to study metabolic diseases, dynamic studies of metabolic pathways via isotopic labeling remains mostly unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, with the booming number of congenital and acquired metabolic disorders identified [71], the need to develop in vitro disease models via patient-derived hiPSCs to study pathogenic mechanisms and screen drugs preclinically is widely increasing. In the field of nucleotide sugar biosynthesis defects, to date only few hiPSC-based studies have been reported, specifically targeting phosphomannomutase 2 (PMM2) deficiency and UDP-glucose pyrophosphorylase (UGP2) deficiency [72][73][74], while they are more extensively used to model other inborn errors of metabolism, such as Pompe disease or mitochondrial disorders [75][76][77][78][79][80][81][82]. Nonetheless, despite the rapidly increasing interest in hiPSCs and hiPSC-derived models to study metabolic diseases, dynamic studies of metabolic pathways via isotopic labeling remains mostly unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence indicates PGC-1α as a central regulator of cardiac metabolism and promoter of oxidative phosphorylation at the expense of glycolysis [77,78]. Whereas AMPK upregulation leads to improved mitochondrial activity and homeostasis in cardiomyocytes [79][80][81][82]. We found that AA-treated iPSC-CMs have undergone significant metabolic changes; genes responsible for the electron transport chain, oxidative phosphorylation, and fatty acid β-oxidation in mitochondria (NDUFV3, COX3, and COX5B) were highly expressed (Additional file 1: Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent examples include the Barth syndrome (BTHS) and Friedreich’s ataxia syndrome (FRDA). An overall list of mtDNA and nucDNA genes contributing to mitochondrial function and corresponding mutations in a disease context have been extensively reported elsewhere ( El-Hattab and Scaglia, 2016 ; Barca et al, 2020 ; Pavez-Giani and Cyganek, 2021 ; Caudal et al, 2022 ). Since these syndromes are based on nuclear or mitochondrial gene mutations with a prominent cardiac phenotype, the iPSC-CM platform provides an excellent tool to study the underlying disease drivers.…”
Section: Insights Into Mitochondrial Cardiomyopathies Using Ipsc-cmmentioning
confidence: 99%